2023
DOI: 10.3390/ijerph20032358
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Mood Effect of Alpha-Lipoic Acid Supplementation in a Nonclinical Elder Sample: An Open-Label Pilot Study

Abstract: Background: Memory disorders are common among elder people, and nonclinical cognitive decline is commonly experienced with age. Preclinical investigations have explored the possible role of alpha-lipoic acid (ALA), a known antioxidant compound abundant in vegetables and animal tissues, in reducing oxidative stress in the aging brain and preventing cognitive decline. However, clinical evidence is limited, and the few existing results are contrasting. In addition, while most of the existing trials have been focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…Studies have shown that ALA may contribute to cognitive health [7]. A further study indicated that higher intake of ALA is associated with better cognitive function in older adults [38]. Fruits and vegetables rich in polyphenolic compounds are beneficial for improving cognitive function and preventing cognitive decline [39].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ALA may contribute to cognitive health [7]. A further study indicated that higher intake of ALA is associated with better cognitive function in older adults [38]. Fruits and vegetables rich in polyphenolic compounds are beneficial for improving cognitive function and preventing cognitive decline [39].…”
Section: Discussionmentioning
confidence: 99%